ANALYSIS OF DISTRIBUTION MANAGEMENT IN ISLAMIC BUSINESS ETHICS (CASE STUDY IN WAROENG SPECIAL SAMBAL YOGYAKARTA 2018). - Yoyok Suyoto Arief; Muhammad Qudri (Journal of Islamic Economics and Philanthropy, 2020)
Distribution is an activity to accelerate the flow of goods or services from the manufacturer to the consumer, then an important factor that should not be ignored is selecting the appropriate distribution channel. Companies can develop several strategies to ensure that their products are well-distributed. Therefore, there needs to be certainty in determining the distribution strategy. This research aims to know the distribution management of products Waroeng Sambal Yogyakarta and its application in the Islamic business ethics perspective. This type of research is qualitative, as is the technique of collecting data in this study using interviews, observations, and doctoral methods. While the analysis method of using SWOT analyses (Strength, Weakness, Opportunity and Threat). The results of the research show that sambal specials implement the First in first out system and apply the POAC management pattern, which is Planning, Organizing, Actuating, and Controlling. As for the practice of the distribution of Warung special Sambal Yogyakarta has implemented Islamic business ethics based on the 5 basic principles of personality. The results of the SWOT analysis were obtained that : (1). Special Sambal Warung can open branches in the city of Yogyakarta and outside Yogyakarta. (2). Add a variety of Menu Sambal. (3). It Can add ease of food ordering mechanism that is based on digital. (4). It Can add a warehouse of raw materials in each branch of the company. (5). It Can add a cooperation network of Supplier raw materials in each branch of the company. (6). It Can increase the number of employees who served in warehousing. (7). It Can be promoted actively through social media. (8). It Can tighten the transmission control of raw materials. (9). It Can multiply the company's increase in HR activities. (10). It Can improve the quality and the mechanism of the provision of raw materials in each branch of the company. (11). It Can periodically contact the quality and quantity of raw materials. (12). Can conduct partners supply raw materials with farmers around the branch company to fulfill the shortage of raw materials due to weather changes.